FAMILIAL CASE OF PURULENT HAEMOPHILUS INFLUENZAE MENINGITIS - T. V. Egorova; L. V. Malkova; P. V. Ashihmin; A. L. Stolbov; A. V. Mokrushin (LLC "Diagnostics and Vaccines", 2017)
Clinical cases of generalized Haemophilus influenzae (Hib) infection with the central nervous system lesions in children from the same family were presented. Methods of the prevention have been proposed in focus of Hib-infection.